Dilema Otoritas dan Kohesi Sosial: Kajian Sosiologis Kebebasan Beragama dan Aliran Baru di Kefamenanu, Nusa Tenggara Timur - Melkianus Suni; Helidorus F. Anin; Nikolaus Uskono (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study situates Kefamenanu, East Nusa Tenggara, as a significant locus for examining religious freedom, given its plural religious landscape and strong cultural traditions, which together create a concrete arena of tension between individual freedom of belief and dominant social norms. The emergence of new religious groups in this context has generated distinctive social, cultural, and institutional responses, markedly different from those in larger urban settings. Unlike previous studies that have tended to label such groups as “heretical” or “deviant” by focusing on doctrinal divergence, this research offers an alternative perspective by foregrounding social interactions, cultural values, the existential motivations of new adherents, and the role of policy frameworks and inter-agency coordination in shaping social relations. Adopting a qualitative case study approach, informants were purposively selected, including community members, officials from the National Unity and Political Agency (Kesbangpol), representatives of the Interfaith Harmony Forum (FKUB), staff of the Office of Religious Affairs, and followers of new religious movements. Data was collected through in-depth interviews, participant observation, and document analysis, and subsequently analyzed thematically. The findings underscore three key aspects: (1) value conflicts between individual religious freedom and cultural norms reinforced by majority pressures; (2) regulatory inefficiencies and weak inter-agency coordination, including the limited authority of FKUB, which exacerbate conflict and miscommunication; and (3) existential motivations as a critical factor driving individuals to join new religious groups despite stigma and social isolation. Overall, the study demonstrates that religious freedom in Kefamenanu is not solely a matter of individual rights but is deeply interwoven with social identity, group integration, and community stability.